2018
DOI: 10.3390/en11040811
|View full text |Cite
|
Sign up to set email alerts
|

Biofuels Production by Biomass Gasification: A Review

Abstract: The production of biofuels from renewable sources is a major challenge in research. Methanol, ethanol, dimethyl ether (DME), synthetic natural gas (SNG), and hydrogen can be produced from syngas which is the result of the gasification of biomasses. Syngas composition varies according to the gasification technology used (such as fixed bed reactors, fluidized bed reactors, entrained flow reactors), the feedstock characteristics, and the operating parameters. This paper presents a review of the predominant biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
156
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 340 publications
(182 citation statements)
references
References 207 publications
(266 reference statements)
2
156
0
1
Order By: Relevance
“…Rajvanshi [5] suggested that fuel moisture, ash content and its elements, particle size, heating value, and bulk density are major fuel properties that affect biomass gasification. Molino et al [6] summarized the effect of these biomass feedstock characteristics on syngas composition; they also discussed the effect of operating conditions, including gasifying agent and equivalence ratio (ER, the ratio of actual A/F value to stoichiometric A/F value). Van der Drift et al [7] suggested that the ER needed to be raised with increasing fuel moisture content in order to keep the gasifier temperature constant.…”
Section: Introductionmentioning
confidence: 99%
“…Rajvanshi [5] suggested that fuel moisture, ash content and its elements, particle size, heating value, and bulk density are major fuel properties that affect biomass gasification. Molino et al [6] summarized the effect of these biomass feedstock characteristics on syngas composition; they also discussed the effect of operating conditions, including gasifying agent and equivalence ratio (ER, the ratio of actual A/F value to stoichiometric A/F value). Van der Drift et al [7] suggested that the ER needed to be raised with increasing fuel moisture content in order to keep the gasifier temperature constant.…”
Section: Introductionmentioning
confidence: 99%
“…These parameters were encoded as presented in Table 1. (5) Aluminium (5) Incineration (16.5) French (6) Organic waste (6) Turkish (7) Wood (7) Arabs (8) Paper (8) African (9) Plastic (9) The numbers in the parentheses represent the coded value.…”
Section: Model Development and Description Of The Input Parametersmentioning
confidence: 99%
“…In this regard, several governments have launched policies to promote the conversion of municipal waste to green precursors or products, many with a specific focus on green fertilizers, bioelectricity, biofuels or bioadsorbents [5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The production of biogas via anaerobic digestion processes has gained increasing interest worldwide due to being environmentally friendly and having a high energy yield [1][2][3][4][5][6][7][8][9][10]. The use of a two-stage process can improve process efficiency in terms of biogas production compared to single-stage anaerobic systems [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%